Organic Syntheses 2005
DOI: 10.1002/0471264229.os082.22
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of (Triphenylphosphoranylidene)‐Ketene from (Methoxycarbonylmethylene)‐Triphenylphosphorane

Abstract: (Triphenylphosphoranylidene)ketene (Methoxycarbonylmethylene)triphenylphosphorane Hexamethyldisilazane Sodium amide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In 2004 and 2005, Schobert et al reported the solid-phase syntheses of 3-acyltetramic acids of the tenuazonic [76] and melophlin family 15 (Scheme 5; Part A) [77], using immobilized (triphenylphosphoranylidene)ketene 16 (Ph 3 PCCO) under mild conditions [78]. This ylide is involved in a Wittig-type cyclization reaction.…”
Section: From Phosphorus Ylide Ph 3 Pccomentioning
confidence: 99%
“…In 2004 and 2005, Schobert et al reported the solid-phase syntheses of 3-acyltetramic acids of the tenuazonic [76] and melophlin family 15 (Scheme 5; Part A) [77], using immobilized (triphenylphosphoranylidene)ketene 16 (Ph 3 PCCO) under mild conditions [78]. This ylide is involved in a Wittig-type cyclization reaction.…”
Section: From Phosphorus Ylide Ph 3 Pccomentioning
confidence: 99%
“…Alternatively it can be easily prepared from commercially available (methoxycarbonylmethylene)triphenylphosphorane by heating it to 65 ˚C with NaHMDS in toluene for 20 hours (Scheme 7.1). 86 It is essential that all the equipment is dry, and that recrystallizations performed for purification purposes are done with dry toluene and under argon to avoid formation of the acid. The Bestmann ylid, if moisture is thoroughly excluded, is stable for long periods of time in a freezer.…”
Section: Late Stage Connections: Bestmann Ylid Linchpin and Ring-closing Metathesismentioning
confidence: 99%
“…Alternatively it can be easily prepared from commercially available (methoxycarbonylmethylene)triphenylphosphorane by heating it to 65 ˚C with NaHMDS in toluene for 20 hours (Scheme 7.1). 86 It is essential that all the equipment is dry, and that recrystallizations performed for purification purposes are done with dry toluene and under argon to avoid formation of the acid. The Bestmann ylid, if moisture is thoroughly excluded, is stable for long periods of time in a freezer.…”
Section: Late Stage Connections: Bestmann Ylid Linchpin and Ring-closing Metathesismentioning
confidence: 99%